Evaluasi Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Akademik Menggunakan Metode Klasifikasi Algoritma C4.5 - Widiastuti, Tri; Karsa, Koko; Juliane, Christina (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
The purpose of this study was to determine the effect of academic services on student satisfaction so that students do not feel disappointed with academic services. This study measures the level of student satisfaction with the existing academic services at Jenderal Achmad Yani University, Cimahi. The data set from the survey results of student satisfaction with academic services at Unjani is used to generate models, rules and accuracy scores for student satisfaction using the Decision Tree C4.5 algorithm data mining classification method, to see the results of the accuracy values ​​of several attributes, namely tangible, empathetic, responsiveness. , reliability and assurance. The results of the tests carried out with the rapidminer application, the accuracy value of the 7 (Seven) Faculties testing at Unjani resulted in a value above 90%, which means that this value indicates that the service that has been running so far is considered very good. Testing student satisfaction surveys must of course be carried out continuously to be able to continue to improve academic services to students for the better.